2012
DOI: 10.3390/membranes2030529
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membranes Modified by Plasma Treatment or Deposition as Solid Electrolytes for Potential Application in Solid Alkaline Fuel Cells

Abstract: In the highly competitive market of fuel cells, solid alkaline fuel cells using liquid fuel (such as cheap, non-toxic and non-valorized glycerol) and not requiring noble metal as catalyst seem quite promising. One of the main hurdles for emergence of such a technology is the development of a hydroxide-conducting membrane characterized by both high conductivity and low fuel permeability. Plasma treatments can enable to positively tune the main fuel cell membrane requirements. In this work, commercial ADP-Morgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…[14] Parallel, we have shown that the hydroxide conductivity of plasma polymers synthesized from triallylamine was decreasing with the average discharge power, which has been attributed not only to the decreasing content of sp 3 N-C functions in films but also hypothetically to the increase of the film density. [14] Lastly, it has been shown in another recent paper by our group that water retention of a commercial hydroxide-exchange membrane could be enhanced by the addition of a triallylamine-based plasma polymerized film on its surface, due to quite poor water sorption and diffusion capabilities of the plasma film directly related to its high cross-linking degree. [15] One objective of the present study is to determine the film density and water swelling of plasma films prepared from triallylamine and to depict their evolution as a function of the average discharge power as the main plasma synthesis parameter.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…[14] Parallel, we have shown that the hydroxide conductivity of plasma polymers synthesized from triallylamine was decreasing with the average discharge power, which has been attributed not only to the decreasing content of sp 3 N-C functions in films but also hypothetically to the increase of the film density. [14] Lastly, it has been shown in another recent paper by our group that water retention of a commercial hydroxide-exchange membrane could be enhanced by the addition of a triallylamine-based plasma polymerized film on its surface, due to quite poor water sorption and diffusion capabilities of the plasma film directly related to its high cross-linking degree. [15] One objective of the present study is to determine the film density and water swelling of plasma films prepared from triallylamine and to depict their evolution as a function of the average discharge power as the main plasma synthesis parameter.…”
Section: Introductionmentioning
confidence: 92%
“…At higher average powers (above 40 W), in the monomer deficient region, the growth rate of films decreases with P A and the structure of the films presents an increasing content of sp 2 N¼C, N-N, and N-O bonds at the expense of sp 3 N-C ones. [14] Moreover comparison between the composition in the bulk and at the film surface has shown that the bulk composition is 5 at.% less enriched in oxygen than the film surface, which is due to a pollution of the latter by atmospheric oxygen once returning the samples to room environment after plasma deposition. [14] In an attempt to introduce quaternary ammonium functions in the films (best hydroxide conducting groups), the latter were treated with methyl iodide (quaternization treatment).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations